THE EFFECT OF DUOLINGO ON THE VOCABULARY OF THE TENTH GRADE STUDENTS OF SMK NEGERI 1 SUKASADA IN ACADEMIC YEAR 2019/2020 - Julianti, R. T.; Hadisaputra, I. N. P.; Dewi, K. S. (Jurnal Pendidikan Bahasa Inggris undiksha, 2020)
This research aimed at investigating whether or not there was any significant effect of using Duolingo on the vocabulary of the tenth-grade students of Senior High School in SMK Negeri 1 Sukasada in academic year 2019/2020, between who taught by Duolingo Mobile Application as a technique and those who taught by using a conventional technique (students’ textbook). This experimental research was conducted by using Post-test Only Control Group Design. The sample was chosen bycluster random sampling and lottery. The samples were X Multimedia 2 as an experimental group and X Multimedia 1 as a control group. There were three kinds of instruments used in this study to collect the data namely lesson plan, vocabulary post-test and weekly observation list. The data were analyzed descriptively and inferentially by using SPSS. Moreover, the effect size was used to see the effect of using Duolingo Mobile Application as a technique on students’ vocabulary. The result of data analysis showed that the mean score of the experimental group was 78.69, while the mean score of the control group was 50.26. In  addition, the Independent samples t-test was revealed that the value of the sig. (2-tailed) was 0.000. It was lower than the standard alpha level (0.05). Since (p) value was lower than the standard alpha level it can be concluded that alternative hypothesis (Ha) was accepted and null hypothesis (H0) was rejected. This result indicates that Duolingo Mobile Application as a technique give a significant effect on on the vocabulary of the tenth-grade students of Senior High School in SMK Negeri 1 Sukasada. Key words: Experimental Research, Duolingo, Vocabulary